Evaluating the Impact of the How‐to Parenting Program on Child Mental Health: A Randomized Controlled Trial in Grade Schools - Joussemet, Mireille; Mageau, Geneviève A.; Larose, Marie‐Pier; Robichaud, Jean‐Michel; Dufour, Sarah; Vitaro, Frank; Koestner, Richard (Wiley, 2026)
The How-to Parenting Program teaches parents how to provide autonomy support, structure, and affiliation, the three components of the parenting style shown to be beneficial for children's mental health. Using a waitlist RCT, we assessed its impact on school-aged children's externalizing and internalizing problems. We also tested whether family composition, participating parents' gender, child age, sex, and baseline mental health modified its effects. Parents (N = 293; 80.20% mothers) were randomly assigned to the French version of the 7-week program or a waitlist condition (i.e., immediate delivery vs. end of study). Parents rated child externalizing and internalizing problems before and after program delivery, as well as 6 and 12 months later. Controlling for unbalanced covariates and baseline levels of problems, multilevel multivariate analyses revealed that compared to the waitlist, the How-to Parenting Program led to greater decreases in children's externalizing problems immediately after program delivery and that this benefit was sustained over at least 6 months. However, decreases in children's internalizing problems were similar across both conditions. Considering this RCT's methodological strengths (e.g., intent-to-treat analyses) and limitations (e.g., intervention diffusion), along with the floor effects inherent to our universal prevention approach, the How-to Parenting Program's benefits, though small in size, indicate that it could prove an effective public mental health prevention strategy.